2012
DOI: 10.1007/s10404-011-0928-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of passive microfluidic mixers incorporating 2D and 3D baffle geometries fabricated using an excimer laser

Abstract: We present new passive microfluidic mixing structures based on 2D and 3D geometries. The primary mechanism of mixing in these devices is based on chaotic advection. The mixers which incorporate 3D structures introduce transverse flow rotation greatly enhancing performance. Simulations and experimental tests were performed over a Reynolds number (Re) range from 0.1 to 20 and showed good agreement. At an Re of 0.1, 90% mixing was achieved in a path length of 32 and 7 mm, for the 2D and 3D geometrical mixers, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…(1) ). This is a considerable improvement compared to the results of former works (11.0 mm 35 and 32.0 mm 29 ), where a higher diffusion coefficient, D = 1 × 10 −10 m 2 /s, was taken into consideration. Clearly, this mixing efficiency and length can be further improved by considering the same diffusion coefficient.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…(1) ). This is a considerable improvement compared to the results of former works (11.0 mm 35 and 32.0 mm 29 ), where a higher diffusion coefficient, D = 1 × 10 −10 m 2 /s, was taken into consideration. Clearly, this mixing efficiency and length can be further improved by considering the same diffusion coefficient.…”
Section: Resultsmentioning
confidence: 61%
“…We numerically investigated the influence of the geometrical characteristics of the design on the mixing performance over a wide range of flow conditions. The performance of the most efficient design was experimentally investigated by means of fluorescence microscopy for a range of diffusion coefficients, 10 −12 < D < 10 −11 m 2 /s, and compared with the previous works 17 30 35 36 . Then, we demonstrated the potential diagnostic value of the micromixer by testing its capability for Red Blood Cells (RBC) lysis.…”
mentioning
confidence: 99%
“…Most theoretical studies of mixing use detailed numerical simulations 11,42 or scaling arguments 19,21 . Here we present an alternative approach, namely a numerical method applied to a simplified mixer-channel setup.…”
Section: Theoretical Mixing Measure Of Amb Arraysmentioning
confidence: 99%
“…The results showed that in the Reynolds number range of 10-50 with the increase of sinusoidal wave amplitude the mixing performance increases, but at the Re = 70 the increase of sinusoidal wave amplitude has not affected the mixing performance. Conlisk and O'Connor [10] studied both numerically and experimentally the mixing performance of the mixer in two and three dimensional states. The Reynolds number varied in the range of 0.1 ≤ Re ≤ 20.…”
Section: List Of Symbols Cmentioning
confidence: 99%